Strategic Management and Analysis of the Sorghum Innovation System in the Tehuledere District, Eastern Amhara, Ethiopia - Teferi, Wondale Habtamu (iRASD Journal of Management, 2024)
This study investigates the challenges faced in managing and strategizing the sorghum innovation system and value chain in the Tehuledere District, situated in the Eastern Amhara Region of Ethiopia. The study utilizes an integrated innovation and value chain framework to examine data from surveys and interviews conducted with 108 participants, encompassing farmers, agro-dealers, traders, and processors. The obtained data encompasses both quantitative and qualitative information. The research analyzes the fundamental components of the sorghum innovation system, encompassing its functionality, structure, capability, and environment. It highlights both the achievements and significant challenges. The challenges include inherent weaknesses in the structure, unexplored potential for innovation and value chain operations, and inadequate implementation of policies in many industries. Moreover, insufficient interactions between stakeholders have led to disparities in information and breakdowns within the market system. To address these issues, the paper proposes adopting policies that prioritize enhancing research and development, extension services, access to funding, and infrastructure development. These initiatives will encourage the development of new ideas and make it easier to establish networks of businesses that add value to products or services. Furthermore, it is imperative to provide ongoing policy support and enhance institutional capacity to ensure the sustainable management and development of the sorghum industry in Ethiopia.